Risk factors for osteoporosis in chronic inflammatory demyelinating polyradiculoneuropathy. Issue 3 (10th September 2018) - Kim, Seung Woo; Choi, Young‐Chul; Kim, Seung Min; Shin, Ha Young
ABSTRACT: Introduction : Chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) patients possess multiple risk factors for osteoporosis, but few studies have evaluated bone mineral density (BMD) in CIDP patients. Methods : We retrospectively compared the BMD of CIDP patients with that of normal controls, and evaluated the clinical factors associated with osteoporosis. Results : Total BMD was lower in CIDP patients than in normal controls ( P = 0.017). In a comparison of 16 osteoporotic CIDP patients with 25 non‐osteoporotic patients, the cumulative prednisolone dose was lower ( P = 0.022) and the duration from disease onset to BMD measurement was shorter ( P = 0.014) in osteoporotic patients than in non‐osteoporotic patients. Function, as measured by modified Rankin scale score within 3 years of the BMD measurement, was worse in osteoporotic than in non‐osteoporotic patients ( P = 0.008). Discussion : BMD in CIDP patients was significantly lower than in normal controls. Functional status rather than cumulative steroid dose was associated with osteoporosis. Muscle Nerve 58 : 407–412, 2018